The hidden curriculum of the special education program in a MARA Junior Science College in Malaysia - Mohd Ihsan, Fatimah (2010)
This study was on the hidden curriculum of the Special Education Program (SEP) at the Gemilang (a pseudonym) MARA Junior Science College. The main objective was to explore facets of the hidden curriculum in a MARA Junior Science College from the perspective of students labeled as gifted. It seeks to answer two research questions: 1) What is the hidden curriculum of the Special Education Program at Gemilang MARA Junior Science College? 2) What are the resultant learning from the hidden curriculum of the Special Education Program of Gemilang MARA Junior Science College? A qualitative approach was chosen to generate data from former students and present teachers of Gemilang MARA Junior Science College. The data was generated from three focus group interviews with 24 former Gemilang MARA Junior College students, individual interviews with four students and 12 teachers, observations of school activities and document review. The data was analyzed manually; codes and categories were identified; and a rich description based on the categories was written to answer the two research questions. To better understand the various strands of schooling experiences that form the hidden curriculum in this particular context, Dewey’s (1938) collateral learning and Cornbleth’s (1990) social context theory were used as a guide in the interpretation of data. The study showed that the hidden curriculum of Gemilang can be described as the routinized and ritualized daily activities,the collaborative efforts in problem solving, the regimented living conditions, the values driven social environment, the tension between doing well and living up to expectations, the selfless approach to nurturing growth of individuals and the disparity between policy making and actual support. These resulted in the learning of intrapersonal and interpersonal skills. The structural and sociocultural context of the SEP which contributed to the hidden curriculum are the physical setting, the academic setting, the affective setting and the social setting of a residential school with an Islamic based daily school routine, a selected student intake and the SEP curriculum with its differentiated instructional and learning orientation. The study concluded that the hidden curriculum facilitated the transmission of social norms while the learning helped mold positive interpersonal and intrapersonal skills in the students in spite of the restrictive nature of the Special Education Program. Among the implications of the study were flexibility and creativity in instruction promotes positive traits in students and teachers. As such, the study recommends that teachers be empowered to be creative and flexible in their instructional approach in order to provide more opportunities for students’ investigative projects.